(untitled) (Economic and Political Thought, 2018)
This paper looks at Schmitt and his critique of liberalism in terms of the question of how the constitutional structure of the modern state can lead to certain contradictions and problems that arise out of the radicalism of the liberal doctrine advanced by the neo-Kantian legal tradition that dominated in Germany in the early twentieth century. I argue that according to Schmitt a return to Hobbes, as well as other modern political thinkers such as Machiavelli and Bodin, was the only means to correct this radicalisation of liberalism to allow for the survival of politics.